Competences in dispute: construction regulation in the I Housing Congress, 1931 - Jordan, Raquel Oliveira (2024)
The article seeks to problematize the debate on the laws regulating construction in São Paulo based on the I Housing Congress of 1931, a moment of rupture in the spheres of legislative deliberation, while new legal provisions were in force. Although focused on housing, as discussed in most of the historiography, the construction regulation was the theme of theses and conferences and the object of controversies in plenary sessions, with outcomes that, frequently, were different from the results indicated in those works. The study analyzes the composition of the professionals present at the congress and the dynamics of the discussions. The aim is to contribute to studies about the topic by discussing the lack of consensus on the regulation in this debate. DOI: https://doi.org/10.1590/2236-9996.2024-6153643-pt https://doi.org/10.1590/2236-9996.2024-6153643-en